Potentially inappropriate prescriptions of antibiotics in geriatric psychiatry—a retrospective cohort study - Pfister, Tabea; Schröder, Sebastian; Heck, Johannes; Bleich, Stefan; Krüger, Tillmann H. C.; Wedegärtner, Felix; Groh, Adrian; Schulze Westhoff, Martin (Frontiers in Psychiatry, 2024)
Introduction: Older patients are frequently affected by infectious diseases and adverse drug reactions (ADRs) of consecutively prescribed antibiotics. Particularly within geriatric psychiatry, high rates of potentially inappropriate prescriptions (PIPs) have been described, significantly complicating pharmacological treatment. Therefore, this study aimed to investigate the frequency and characteristics of antibiotic PIPs in geriatric psychiatry. Methods: Medication charts of 139 patient cases (mean age 78.8 years; 69.8 % female) receiving antibiotic treatment on a geriatric psychiatric ward were analyzed. Utilizing previously published definitions of antibiotic PIPs, adequacy of the antibiotic prescriptions was subsequently assessed. Results: 16.3 % of all screened patient cases (139/851) received an antibiotic treatment during their inpatient stay. 59.5 % of antibiotic prescriptions were due to urinary tract infections, followed by pulmonary (13.3 %) and skin and soft tissue infections (11.3 %). 46.7 % of all antibiotic prescriptions fulfilled at least one PIP criterium, with the prescription of an antibiotic course for more than seven days as the most common PIP (15.3 %). Discussion: Antibiotic PIPs can be considered as a frequent phenomenon in geriatric psychiatry. Especially the use of fluoroquinolones and cephalosporins should be discussed critically due to their extensive side effect profiles. Due to the special characteristics of geriatric psychiatric patients, international guidelines on the use of antibiotics should consider frailty and psychotropic polypharmacy of this patient population more closely.